Italy : Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses main findings of the Detailed Assessment of Observance of International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation in Italy. Italy exhibits a high level of implementation of the IOSCO principles. Overall the legal and regulatory framework is sound, and the regulatory authorities have developed extremely sophisticated arrangements for off-site supervision that have resulted in a robust system of supervision. However, these arrangements need to be complemented by additional on-site inspections to make the system more effective. In addition, the enforcement strategy should be continuously monitored to ensure that there is the right mix of tools to affect behavior.